Tradisi Pengobatan Mambang Deo-Deo Dalam Pandangan Akidah Islam di Kepenghuluan Teluk Pulai Kecamatan Pasir Limau Kapas Kabupaten Rokan Hilir - Syukri Syukri (AL-HIKMAH:Jurnal Theosofi dan Peradaban Islam, 2021)
This thesis is entitled "Tradition of Treatment of MambangDeo-deo in the View of the Islamic Faith in the PenghuluanTelukPulai District, PasirLimauKapas District, RokanHilir Regency". This tradition is a treatment that is carried out with the supernatural power of a bomo or shaman, by summoning a supernatural being or called Mambang who is considered to be able to treat or cure a sick patient. This study uses a qualitative method and conducts research in a field research that comes from religious leaders, bomo or shamans from the treatment of MambangDeo-deo, and the chairman of the Malay Traditional Institute. Then supported by literature studies related to theoretical opinions. Allah swt does tell his creatures to try, because without effort it is impossible to achieve anything, as well as in the case of treatment for every disease there is a cure, if treated with Allah's permission, it will heal. However, sometimes there are deviations in carrying out treatment and contrary to Islamic creed, as contained in the MambangDeo-deo medical tradition where in practice there are deviations that have the potential to be doubtful (unclear). In carrying out treatment, it should be done without violating the rules of Islamic law. This shows that medical practices that are contrary to the main teachings of Islam must be rejected because they are contrary to Islamic teachings.